We are Family: A Feasibility and Acceptability Study of an HIV Prevention Intervention With the House Ball and Gay Family Communities. (15th December 2021) - Arnold, Emily A.; Saberi, Parya; Wong, Jeffrey O.; Pollack, Lance M.; Neilands, Torsten B.; Benjamin, Michael; Lockett, Gloria; Kegeles, Susan M.
Abstract : Background: Black and Latinx sexual minority youth are disproportionately affected by HIV. The House Ball and gay family communities encompass sexual and ethnic minority youth who form chosen families that promote protective HIV-related health behaviors. We conducted a small-scale trial of the We Are Family intervention, leveraging these existing social dynamics to address HIV. Methods: From September 2018 to September 2019, we enrolled N = 118 for baseline and 6-month follow-up assessments. Eligible participants were 18 years or older, San Francisco Bay Area residents, members of a house or gay family or ball attendees in the past year, smartphone users, and sexually active. The intervention included one 2-hour in-person group session, community-level events, a mobile health app, and a dedicated service provider. Results: Ninety-seven percent of our participants were people of color, 94% were retained through follow-up. 73% attended at least 1 group session, 100% used the mobile health app, and 56% attended a community-level event. Modest changes were observed baseline to follow-up: among all participants, any condomless anal intercourse past 3 months (74.6%–66.7%, P = 0.064); among HIV-negative participants (N = 82) HIV testing past 6 months (80.7%–87.2%, P = 0.166); among HIV-positive participants (N = 34) receiving HIV primary care past 6 months (64.5%–78.8%, P = 0.139), and adherent to ART past 30 days (22.6%–28.1%, P = 0.712). 86% would be willing to refer a friend to the app, and 65% found the app to be personally relevant. Conclusions: We Are Family reaches and retains its target population, is feasible, acceptable, and shows promise for improving HIV-related health behavior.